Biology of plant volatiles - Pichersky, Eran.; Dudareva, N. A. e (Boca Raton, FL : CRC Press, 2020)
Plant volatiles--compounds emitted from plant organs to interact with the surrounding environment--play essential roles in attracting pollinators and defending against herbivores and pathogenes, plant-plant signaling, and abiotic stress responses. Biology of Plant Volatiles, with contributions from leading international groups of distinguished scientists in the field, explores the major aspects of plant scent biology. Responding to new developments in the detection of the complex compound structures of volatiles, this book details the composition and biosynthesis of plant volatiles and their mode of emission. It explains the function and significance of volatiles for plants as well as insects and microbes whose interactions with plants are affected by these compounds. The content also explores the biotechnological and commercial potential for the manipulation of plant volatiles. Features: Combines widely scattered literature in a single volume for the first time, covering all important aspects of plant volatiles, from their chemical structures to their biosynthesis to their roles in the interactions of plants with their biotic and abiotic environment Takes an interdisciplinary approach, providing multilevel analysis from chemistry and genes to enzymology, cell biology, organismal biology and ecology Includes up-to-date methodologies in plant scent biology research, from molecular biology and enzymology to functional genomics This book will be a touchstone for future research on the many applications of plant volatiles and is aimed at plant biologists, entomologists, evolutionary biologists and researchers in the horticulture and perfume industries.
OCLC-licensed vendor bibliographic record.
Keywords: Flowers -- Morphogenesis -- Molecular aspects; Flowers -- Odor; Plant osmophors; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / Zoology / Entomology; SCIENCE / Life Sciences / Biology / Molecular Biology